Hubungan Pengetahuan dan Sikap Pasien terhadap Perilaku Hidup Bersih dan Sehat (PHBS) dengan Luka Diabetes Melitus - Taufandas, Maruli; Supriadi, Supriadi; Akhmadi, Akhmadi (ProHealth Journal, 2024)
People with diabetes mellitus have hope for a good quality of life, this must be supported by good attitudes and knowledge. Good attitudes and knowledge will be reflected in the clean and healthy living behavior that is carried out by patients in everyday life. Objective To understand the relationship between patient knowledge and attitudes towards clean and healthy living behavior with diabetes mellitus wounds at the Lendang Nangka Public Health Center. The design in this study uses correlational with a cross-sectional approach. The sampling method is total sampling with a total of 32 people and bivariate analysis using Spearman Rank. Results: The results of the study obtained a p-value of 0.000 for knowledge and 0.001 for patient attitudes or a significance level of p-value <0.05, so there is a relationship between patient knowledge and attitudes towards clean and healthy living behavior and diabetes mellitus wounds. Conclusion there is a relationship between patient knowledge and attitudes towards clean and healthy living behavior with diabetes mellitus wounds at the Lendang Nangka Public Health Center.